EFEKTIVITAS PENYALURAN BANTUAN LANGSUNG TUNAI (BLT) DANA DESA DI DESA PULAU KOPUNG SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2023 - Putra, Aldra; Nasution, Hazqon Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the findings of a phenomenon related to the distribution of BLT village funds, namely the ineffectiveness of the distribution and data collection of BLT village fund beneficiary families (KPM). This study aims to determine the effectiveness and factors that hinder the Effectiveness of BLT Village Fund Distribution in Pulau Kopung Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency in 2023. This research is a qualitative study. Data sources were obtained from twelve research informants through interview techniques. The results of this study found that: The Effectiveness of the Distribution of Direct Cash Assistance (BLT) Village Funds in Pulau Kopung Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency in 2023 is still not effective, even though the distribution of BLT village funds has been implemented in accordance with PerKaDes Article 1 No. 20 of 2023 concerning BLT, and has been distributed from January to December 2023, but it is still not effective because it has not met the indicators of timeliness and accuracy of targets even though most KPM are eligible as recipients, but because there are still some KPM using family or insiders in the village government. The factors that hinder the Effectiveness of the Distribution of Direct Cash Assistance (BLT) Village Funds in Pulau Kopung Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency in 2023 are the delay in the distribution of BLT Village Funds. The factor of the attitude of the implementer who is not optimal in recording KPM data and the factor of the absence of socialization from the beginning before the implementation until the distribution of the BLT Village Funds, so that the community, especially KPM, do not clearly understand the intent and purpose of this BLT Village Fund Program. Keywords: : BLT, Timeliness, Accuracy in Making Choice, Accuracy in Targetin